2002
DOI: 10.1046/j.1474-919x.2002.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of Common Goldeneye Bucephala clangula females in relation to age and lifespan

Abstract: We studied the effects of female age and length of lifespan on reproductive performance in the Common Goldeneye Bucephala clangula, a precocial species with self‐feeding chicks. Dependent variables studied were the occurrence of failed nesting attempts and non‐breeding years, clutch size, nesting and hatching success, female condition and recovery rate of offspring. To avoid misinterpretations resulting from age‐dependent quality changes in the cohorts, individuals with different lifespans were separated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…Our results suggest that substantial heterogeneity in individual quality exists in goldeneyes breeding in Alaska, as indicated by extensive support for individual covariate effects in juvenile demographic parameters (φ J and ψ PB ), and the positive covariation among demographic components observed in adults (Cam et al ). The latter finding is consistent with other goldeneye studies (Dow and Fredga , Milonoff et al ). Prior nest success (NS) was positively associated with adult female detection, and breeding and survival probabilities, though the confidence intervals overlapped zero slightly in the latter two parameters.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results suggest that substantial heterogeneity in individual quality exists in goldeneyes breeding in Alaska, as indicated by extensive support for individual covariate effects in juvenile demographic parameters (φ J and ψ PB ), and the positive covariation among demographic components observed in adults (Cam et al ). The latter finding is consistent with other goldeneye studies (Dow and Fredga , Milonoff et al ). Prior nest success (NS) was positively associated with adult female detection, and breeding and survival probabilities, though the confidence intervals overlapped zero slightly in the latter two parameters.…”
Section: Discussionsupporting
confidence: 93%
“…Both lower nest success and increased use of parasitic egg‐laying would reduce detection probability of two‐year‐olds relative to older females. Age‐related variation in detection probability may account for the discrepancy between the high probability of recruitment at two years of age we found, and other goldeneye studies that reported average age of first breeding closer to three‐years‐old (Eadie et al , Milonoff et al ). These latter studies based their estimates of age at first breeding solely on observations of observed‐first time breeding attempts, which are likely to be biased high due to the lower detection probability of two‐year‐olds.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Hepp and Kennamer 1993;Milonoff et al 2002;Blums et al 2005). Winter body condition is, however, also a parameter of great importance, likely to affect duck survival during that season specifically (e.g.…”
Section: Introductionmentioning
confidence: 99%